1953
DOI: 10.1080/17470215308416620
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Adaptation on Absolute Threshold Measurements for Olfactory Stimuli

Abstract: A group-test method of determining the mean absolute olfactory threshold to a test stimulus for a group of subjects is described. Probit analysis is employed t o evaluate the results. This technique is utilized to measure the change in sensitivity to the test stimulus due to adaptation to the masking stimulus. When the values of the logarithm of the threshold concentration of the test stimulus are plotted against the logarithm of the concentration of the masking stimulus for a pair of odorous materials, a stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1956
1956
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Observations were made somewhat on the lines described by Cheesman & Mayne (1953) by direct smelling of 20 ml. odorant in a wide-neck 200 ml.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations were made somewhat on the lines described by Cheesman & Mayne (1953) by direct smelling of 20 ml. odorant in a wide-neck 200 ml.…”
Section: Methodsmentioning
confidence: 99%
“…Gamble (1896), reviewing the results of his contemporaries, wrote: 'a subject whose organ is fatigued by the continuous smelling of tincture of iodine can sense ethereal oils and ethers almost or quite as well as ever, oils of lemon, turpentine and cloves but faintly, and common alcohol not at all'. The same idea still persists, and Cheesman & Mayne (1953) have described work on olfactory adaptation which had the ultimate aim of classifying the odorants on a basis of the adaptation they mutually induce. Just how the adaptation that a pair of smells will induce for each other varies with the likeness of the two smells appears hitherto not to have been defined.…”
mentioning
confidence: 99%
“…Short-term adaptation is usually measured either as a threshold change (see, e.g., Berglund et aI., 1971;Cheesman & Mayne, 1953) or as a change in perceived intensity of suprathreshold concentrations (see, e.g., Cain, 1970). Although threshold shifts are often used to predict shifts at suprathreshold levels, these methods are not necessarily interchangeable.…”
Section: Experiments 2 Long-term Exposure Adaptation and Recoverymentioning
confidence: 99%
“…Although the use of an olfactometer produces the most reliable results (Stone, 1963), the sniff method such as that described by Engen (1961), also produces highly consistent results. The sniff method was used in the present investigation because stimuli of the same concentration can easily be reproduced from session to session.Another set of olfactory threshold experiments has been conducted to study adaptation effects, the influence of stimulus parameters on threshold, and odor similarity (Cheesman & Mayne, 1953;Moncrieff, 1956;Stuiver, 1958). Engen (1960) used lowering of absolute threshold as an index of practice effects: in addition, he found that verbal instructions to S influenced the reported threshold, but no attempt was made to analyze sensitivity independent of this response-biasing phenomenon.…”
mentioning
confidence: 99%
“…Another set of olfactory threshold experiments has been conducted to study adaptation effects, the influence of stimulus parameters on threshold, and odor similarity (Cheesman & Mayne, 1953;Moncrieff, 1956;Stuiver, 1958). Engen (1960) used lowering of absolute threshold as an index of practice effects: in addition, he found that verbal instructions to S influenced the reported threshold, but no attempt was made to analyze sensitivity independent of this response-biasing phenomenon.…”
mentioning
confidence: 99%